Psychometric properties of the Persian version of nutrition literacy scale in the elderly - Fatemeh Sharifnia; Mohtasham Ghaffari; Sakineh Rakhshanderou (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Aging and chronic diseases associated with nutrition are increasing in the world; therefore, access to a tool for assessing nutritional literacy in the elderly is necessary. Therefore, the present study was carried out with the aim of psychometric evaluation of nutritional literacy in the elderly. MATERIALS AND METHODS: This study was carried out to psychometric testing of the Nutrition Literacy Scale (NLS), through the validity and reliability of the tool in 280 elderly people (60 years of age and older) in Tehran. The validity of this tool was determined through the methods of translation, face and content and reliability of the tool through the methods of test-retest and internal consistency. Finally, the tool was analyzed using SPSS software version 16. RESULTS: In this study, content validity index (CVI) was calculated for each item; CVI average was 0.86.5. To determine the reliability of the tool, interclass correlation coefficient was calculated by measuring the instrument's stability, and it was 0.92. Exploratory factor analysis confirmed the existence of six factors in the questionnaire, which was named nutritional information, healthy nutrition, calorie intake, organic foods, saturated fats, and unit size, which explains 43% of the total variance. Furthermore, in the internal consistency assessment, the questionnaire was completed by 280 elderly people, and the Cronbach's α coefficient was 0.80. CONCLUSION: Based on the results obtained in the reliability and validity assessment, NLS in Iranian elderly has a desirable reliability and validity. This questionnaire has been translated into Persian for the first time. The results of this study provide a standard tool for assessing nutritional literacy status in Persian language communities.